Gender differences: are there differences even in Pediatrics and Neonatology? - Francesco Tandoi; Massimo Agosti (Hygeia Press di Corridori Marinella, 2012)
The approach to research on gender differences in an evolutionary context has always been complex. Many factors, from those initially linked to preliminary considerations about the differences between the sexes in different historical and cultural moments have often influenced studies of this type. Gender Medicine, consolidated in the United States as a research field since the 1980s, studies the way in which membership in gender, male or female, affects the development and impact of disease and response to therapy. We can say that this is a new, transverse dimension of Medicine that assesses gender differences in physiology and pathophysiology of many clinical diseases, with the aim of reaching treatment decisions based on evidence in both men and women. In an historical moment focused on the individualization/personalization of care, among the objectives that modern health care has been given, there is this research aimed at identifying as early as possible gender-related diseases with the aim of identifying causes and possible methods of intervention. It leads to defining a kind of Medicine, a recent branch of biomedical science, that focuses on recognizing and analyzing the differences arising from the belonging to a gender, male or female, from several aspects: organic, functional, psychological, pharmacological, social and cultural. A gender approach to Medicine can reduce the level of error in medical practice, promote therapeutic appropriateness, improve and customize therapies and generate savings for healthcare systems. These effects have been demonstrated for adults and need to be confirmed during infancy and childhood. The purpose of this discipline is to innovate and guarantee everyone, man or woman, newborn and children, the best possible treatment based on scientific evidence.